Role of Na+/K+-ATPase in ischemic stroke: in-depth perspectives from physiology to pharmacology - Zhu, Mengyuan; Sun, Haijian; Cao, Lei; Wu, Zhiyuan; Leng, Bin; Bian, Jinsong (Journal of molecular medicine (Berlin, Germany), 2022)
Na + /K + -ATPase (NKA) is a large transmembrane protein expressed in all cells. It is well studied for its ion exchanging function, which is indispensable for the maintenance of electrochemical gradients across the plasma membrane and herein neuronal excitability. The widely recognized pump function of NKA closely depends on its unique structure features and conformational changes upon binding of specific ions. Various Na + -dependent secondary transport systems are rigorously controlled by the ionic gradients generated by NKA and are essential for multiple physiological processes. In addition, roles of NKA as a signal transducer have also been unveiled nowadays. Plethora of signaling cascades are defined including Src-Ras-MAPK signaling, IP3R-mediated calcium oscillation, inflammation, and autophagy though most underlying mechanisms remain elusive. Ischemic stroke occurs when the blood flow carrying nutrients and oxygen into the brain is disrupted by blood clots, which is manifested by excitotoxicity, oxidative stress, inflammation, etc. The protective effect of NKA against ischemic stress is emerging gradually with the application of specific NKA inhibitor. However, NKA-related research is limited due to the opposite effects caused by NKA inhibitor at lower doses. The present review focuses on the recent progression involving different aspects about NKA in cellular homeostasis to present an in-depth understanding of this unique protein. Moreover, essential roles of NKA in ischemic pathology are discussed to provide a platform and bright future for the improvement in clinical research on ischemic stroke.